2007
DOI: 10.2193/2006-004
|View full text |Cite
|
Sign up to set email alerts
|

Uneven Rates of Landscape Change as a Source of Bias in Roadside Wildlife Surveys

Abstract: Roadside survey data have been used frequently to assess species occurrence and population trends and to establish conservation priorities. However, most studies using such data assume that samples are representative of either the amount of habitat or its rate of change at larger spatial scales. We tested both of these assumptions for the Breeding Bird Survey (BBS) from 1974 to 2001 in New Brunswick, Canada. Our study focused on mature forest—a cover type that we predicted would be characterized by rapid chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 49 publications
4
60
0
Order By: Relevance
“…Furthermore, differences in geographic scales of comparison and units of measure make it difficult to directly compare the magnitude of bias between studies; thus, future work may benefit from reporting biases over multiple distance classes as we have done here. Despite scale differences, our results are generally of a magnitude similar to biases reported by Betts et al (2007) in New Brunswick (13.5%-22.5% bias) and biases of up to 30% in representing some cover types in the boreal forest (Matsuoka et al 2011). Similarly, Veech et al (2012) showed biased representation of some developed landcover classes in the 2%-6% range, which falls at the low range of overrepresentation of anthropogenic disturbances we describe.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Furthermore, differences in geographic scales of comparison and units of measure make it difficult to directly compare the magnitude of bias between studies; thus, future work may benefit from reporting biases over multiple distance classes as we have done here. Despite scale differences, our results are generally of a magnitude similar to biases reported by Betts et al (2007) in New Brunswick (13.5%-22.5% bias) and biases of up to 30% in representing some cover types in the boreal forest (Matsuoka et al 2011). Similarly, Veech et al (2012) showed biased representation of some developed landcover classes in the 2%-6% range, which falls at the low range of overrepresentation of anthropogenic disturbances we describe.…”
Section: Discussionsupporting
confidence: 83%
“…Several previous studies have found variable bias in habitat representation and/or disturbance rates (Bart et al 1995, Keller and Scallan 1999, Lawler and O'Connor 2004, Betts et al 2007, Harris and Haskell 2007, Matsuouka et al 2011, Veech et al 2012. Our analyses suggested that bias was greatest in areas immediately along roadsides, which corresponds to work by Keller and Scallan (1999), who found a greater rate of increase in urban area along roadsides (0-200 m) than off-road areas (200-1600 m) in Maryland.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, there are concerns when BBS data are used to (1) generate population size estimates (e.g., Partners in Flight; Blancher et al 2013), because roads influence bird behavior (Matsuoka et al 2011) and sound transmission relative to forest interiors (Haché et al 2014, and (2) assess trends for species that are systematically arriving earlier than the June survey period creating declines in population size owing to a change in phenology, but not abundance (Inouye et al 2000, Parmesan 2007). The BBS in boreal Canada also suffers from a nonrandom distribution of routes, poor habitat representation (Matsuoka et al 2011), and biased representation of disturbance rates (Betts et al 2007, Machtans et al 2014, Van Wilgenburg et al 2015, Handel and Sauer 2017. The degree to which these add variance to the data and reduce power and precision is a concern.…”
Section: Introductionmentioning
confidence: 99%